إجماعات الشوكاني في نيل الأوطارجمعاً ودراسةمن أول كتاب الطهارة إلى نهاية كتاب الصلاةرسالة مقدمة لنيل درجة الماجستير في الفكر الإسلاميImam Syawkany's Consensus in His Book Naylul Author, from the chapter of Thaharah to the Chapter of Salah - Hakim, Abdul, Dr. M. Muinudinillah Basri, M.A (2014)
Actually in quoting of ijma'(consensus), it is in desperate need of studying and researching its validity. The consensus often solves many disagreed reasons. Because it's appointed reasoning is stronger and more accurate than Al Quran and Al Hadith but unfortunately, ijma'has little attention in the study and test. The Ummah need to know the truth of quoting ijma' and it is not wise to leave the matter floating in uncertainty. This is the role of the scholars and researchers, wherein they can restore the understanding of kholaf generation to the understanding of the salaf generation as well as move the attention of the people towards the scholars dispute to their agreement.This study uses the deductive method, that discusses the problem from its roots, rules and their application in the book Naylul Author, and the inductive method which concludes many opinions in various matters. Including the important result of this study is that Imam Syawkany insists consensus in the book of Thaharah and Salahas many as forty three problems, thirty seven of them are proven valid but six of them are proven invalid. Keywords : Ijma, Shawkany, Naylul Author